The global jukebox : the international music industry - Burnett, Robert, 1956- (Communication and society (Routledge (Firm)), 1996)
Popular music is with us constantly. It is part of our everyday environment and in global terms it is now perhaps the most universal means of communication. The Global Jukebox is the first comprehensive study of the international music industry at a time of great change, as the entertainment industry acknowledges its ever growing global audience. Robert Burnett provides an international overview of the music business and its future prospects in the UK, Northern Europe and the United States and Canada. He examines the relationship between local and global cultures and between concent.